Progressive Interpretation: The Meaning of Al-Miskin in the Tafsir Surah Al-Ma'un by Nur Khalik Ridwan - Nopriani Hasibuan; Mukhlis Sore (Penerbit Hellow Pustaka, 2025)
Nur Khalik Ridwan's tafsir of Surah Al-Maun examines the term al-miskīn in the context of social justice in Indonesia, emphasizing that poverty is not destiny, but rather the result of an unequal social structure. This study aims to reexamine the meaning of al-miskīn through Nur Khalik Ridwan's progressive interpretation, particularly in his Interpretation of Surah Al-Ma'un, and to analyze its relevance to the social reality of Indonesian society. This study uses a qualitative method with a library research type, making Ridwan's Tafsir Surah al-Ma'un the primary source. Through the adabi al-ijtima‘i approach and the tafsir tahlili method, Ridwan understands al-miskīn not only as individuals who are economically poor, but as symbols of the oppressed class produced by an unjust social system and rejects the notion of poverty as destiny. The results of the study show that Ridwan's interpretation is a form of renewal of Qur'anic interpretation that bridges the text and the social context, sides with the mustadh‘afīn (the oppressed), and reflects the spirit of renewal of Islamic thought in Indonesia. Ridwan offers a reading that encourages social change and structural liberation, in which ith'amu miskīn (feeding the poor) is understood as a symbol of the struggle against injustice.